2013
DOI: 10.1136/bmjopen-2012-002264
|View full text |Cite
|
Sign up to set email alerts
|

Access to improved water and its relationship with diarrhoea in Kathmandu Valley, Nepal: a cross-sectional study

Abstract: ObjectiveTo assess the associations between diarrhoea and types of water sources, total quantity of water consumed and the quantity of improved water consumed in rapidly growing, highly populated urban areas in developing countries.DesignCross-sectional analysis using population-representative secondary data obtained from an interview survey conducted by the Asian Development Bank for the 2009 Kathmandu Valley Water Distribution, Sewerage and Urban Development Project.SettingKathmandu Valley, Nepal.Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 13 publications
4
33
3
Order By: Relevance
“…These results indicated that the water market was well established in the valley within a period of six years and that water buying has been a widely practiced coping strategy as reported by Pasakhala et al [15]. In contrast to 26% of households in 2009 [28], our study observed that none of the households (see Supplementary Materials, Table S4) relied on piped water alone. These wide differences between the studies, conducted within a short time span, suggests that households' dependency on different water sources changes swiftly in water scarce incessantly populating areas, and that real situations should be scanned properly before planning any related projects or policies.…”
Section: Discussioncontrasting
confidence: 53%
“…These results indicated that the water market was well established in the valley within a period of six years and that water buying has been a widely practiced coping strategy as reported by Pasakhala et al [15]. In contrast to 26% of households in 2009 [28], our study observed that none of the households (see Supplementary Materials, Table S4) relied on piped water alone. These wide differences between the studies, conducted within a short time span, suggests that households' dependency on different water sources changes swiftly in water scarce incessantly populating areas, and that real situations should be scanned properly before planning any related projects or policies.…”
Section: Discussioncontrasting
confidence: 53%
“…Nepal is a small, beautiful landlocked country, located entirely in the Ganges basin, bordering with India in the east, west, and south, and China in the north. The northern border region of Nepal contains 200 peaks of more than 6,000 m and 13 peaks of more than 8,000 m high, including Mount Everest (Shrestha & Aryal, 2011;Shrestha et al, 2013). The Nepal Himalaya covers approximately 35% of the total area and contains a large number of glaciers and glacial lakes that provide huge natural storage of freshwater in the form of ice (WECS, 2011;Shrestha et al, 2013).…”
Section: Nepal's Landscapementioning
confidence: 99%
“…The northern border region of Nepal contains 200 peaks of more than 6,000 m and 13 peaks of more than 8,000 m high, including Mount Everest (Shrestha & Aryal, 2011;Shrestha et al, 2013). The Nepal Himalaya covers approximately 35% of the total area and contains a large number of glaciers and glacial lakes that provide huge natural storage of freshwater in the form of ice (WECS, 2011;Shrestha et al, 2013). Nepal is also known as the Land of Everest and contains approximately 3,252 glaciers with a total coverage of 5,323 km 2 and 481 km 3 of estimated ice reserves (Mool et al, 2001;Bajracharya & Shrestha, 2011;WECS, 2011).…”
Section: Nepal's Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in water constraint situations as in the KV, water utilities supplement the network with sources such as the deep tube wells without treating or a limited treatment (only plain sedimentation and/or filtration). Although increasing the quantity of water supplied has been associated with reduced diarrheal contaminations 15) , supplementing the IWS system with no/limited treatment can increase the chances of other diseases causing bacterial species such as Vibrio, Salmonella, and Shigella to release into the network ( Table 1).…”
Section: Iii_32mentioning
confidence: 99%